Lymphatic Vessel Regression and Its Therapeutic Applications: Learning From Principles of Blood Vessel Regression - Masood, Faisal; Bhattaram, Rohan; Rosenblatt, Mark I.; Kazlauskas, Andrius; Chang, Jin-Hong; Azar, Dimitri T. (Frontiers in Physiology, 2022)
Aberrant lymphatic system function has been increasingly implicated in pathologies such as lymphedema, organ transplant rejection, cardiovascular disease, obesity, and neurodegenerative diseases such as Alzheimer’s disease and Parkinson’s disease. While some pathologies have a component of lymphatic vessel regression and dysfunction, others stand to benefit from therapeutic lymphatic regression. Despite its importance, our understanding of lymphatic vessel regression is far behind that of blood vessel regression. Herein, we review the current understanding of blood vessel regression to identify several hallmarks of this phenomenon that can be extended to further our understanding of lymphatic vessel regression. We also summarize current research on lymphatic vessel regression and an array of research tools and models that can be utilized to advance this field. Additionally, we discuss the roles of lymphatic vessel regression and dysfunction in select pathologies, highlighting how an improved understanding of lymphatic vessel regression may yield therapeutic insights for these disease states.